Juvenile delinquency, crime and social marginalization : social and political implications - Basto Pereira, Miguel; Maia, Angela da Costa (Emerald Publishing Limited, 2017)
This book examines the psychosocial, legal, and familial factors at play in the persistence in crime and social marginalization in adults with a history of juvenile delinquency, setting out the political and social implications, and delineating new lines of research.
Keywords: Juvenile delinquency -- Social aspects.; Juvenile delinquency -- Political aspects.; Criminal behavior -- Social aspects.; Criminal behavior -- Political aspects.; elektronické knihy; electronic books